The threshold effects of inflation rate, interest rate, and exchange rate on economic growth in Nigeria - Olajide O. Oyadeyi; Tolulope T. Osinubi; Munacinga Simatele; Oluwadamilola A. Oyadeyi (Cogent Economics & Finance)
The study examines the optimum threshold effects of interest rates, inflation rates, and exchange rates in stimulating economic growth in Nigeria. The study adopts the threshold regression technique to ascertain the optimal benchmark beyond which these macroeconomic variables hurt growth. The results of interest rate-economic growth thresholds suggest targeting an average monetary policy rate of 16.5%, a prime lending rate of 20%, and a maximum lending rate of 30%. The results of inflation-economic growth thresholds suggest targeting a headline inflation rate of 9%, while core inflation of 8.7% and food inflation of 12.7% are all growth-enhancing for Nigeria. Lastly, the results of exchange rate-economic growth thresholds suggest that targeting a quarterly depreciation of not more than 2.4% for the official exchange rate and a quarterly depreciation of not more than 2.5% for the unofficial exchange rate are growth-enhancing for Nigeria. The results offer policymakers valuable insights, emphasising the significance of exchange rate management, interest rate management, and inflation rate management in promoting growth and emphasising the necessity of reforms to diversify exports, strengthen institutions, and improve the efficacy of monetary policy. Therefore, the study suggests that the Nigerian government should target the obtainable thresholds for growth to become sustainable.